2021
DOI: 10.3390/healthcare9060768
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Scuba Diving on Microleakage of a Class II Composite Restoration: An In-Vitro Study

Abstract: Persistent pressure change is a common phenomenon within scuba diving with various medical and dental sign side effects. This study evaluates the effect of simulated pressure change due to scuba diving on the microleakage of class II composite restoration. In our methodology, a total number of 150 intact bicuspids are divided into two main groups (A and B), and prepared for a class II composite restoration. The samples of each main group are divided into five subgroups to be prepared with different liners. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 26 publications
0
3
0
Order By: Relevance
“…12 CBCT is increasingly used for accurate localization of impacted canine teeth and estimation of the risk of root resorption in adjacent incisors. 1315…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…12 CBCT is increasingly used for accurate localization of impacted canine teeth and estimation of the risk of root resorption in adjacent incisors. 1315…”
Section: Introductionmentioning
confidence: 99%
“…12 CBCT is increasingly used for accurate localization of impacted canine teeth and estimation of the risk of root resorption in adjacent incisors. [13][14][15] For long, conventional radiographic modalities have been applied for diagnosis and orthodontic treatment planning of impacted canine teeth. However; they are gradually replaced with CBCT.…”
Section: Introductionmentioning
confidence: 99%
“…It has been estimated that 60%–70% of the general population experiences at least one sign or symptom of TMD in their life time; however, only 5% of individuals show severe TMD that requires treatment (Poveda Roda et al, 2007 ). Recent studies showed that psychosocial factors such as stress, anxiety, alexithymia, and catastrophizing could affect the onset of TMD and its response to treatment (De la Torre Canales et al, 2020 ; Rollman & Gillespie, 2000 ; Sadrzadeh‐Afshar et al, 2023 ; Shahnavazi et al, 2021 ). Different malocclusions have also been a controversial risk factor for TMD (Manfredini et al, 2017 ; Salari et al, 2024 ).…”
Section: Introductionmentioning
confidence: 99%